Consequences and Prognosis of Running-Related Knee Injuries Among Recreational Runners. Issue 1 (January 2022) - Cloosterman, Kyra L.A.; Fokkema, Tryntsje; de Vos, Robert-Jan; Bierma-Zeinstra, Sita M.A.; van Middelkoop, Marienke
Abstract : Objective: To investigate the consequences and prognostic factors of running-related knee injuries (RRKIs) among recreational runners. Design: Prospective cohort study. Setting: This study is part of a randomized-controlled trial (RCT) on running injury prevention among recreational runners. At baseline during registration for a running event (5-42 km), demographic and training variables were collected. Participants who reported a new RRKI during follow-up were sent a knee-specific questionnaire at 16 months (range 11.7-18.6) after baseline. Participants: One hundred thirty-eight runners who reported a new RRKI during the RCT on injury prevention responded to the knee-specific questionnaire. Assessment of Risk Factors: To determine the association between potential prognostic factors and time to recovery of an RRKI, a Cox regression analysis was performed. Main Outcome Measures: Time to recovery and prognostic factors of RRKIs. Results: At 16 months after registration, 71.0% of the participants reported full recovery, with a median time to recovery of 8.0 weeks. Most participants reported iliotibial band syndrome (23.2%) or osteoarthritis (OA)/degenerative meniscopathy (23.2%) as cause of their injury. Male sex was associated with a shorter time to recovery [hazard ratio (HR) 1.84; 95% confidence interval (CI), 1.14-2.97], while suffering knee OA was associated with a longer time to recovery (HR 0.17; 95% CI, 0.06-0.46). Conclusions: Nonrecovered participants adjusted running speed more often and had knee imaging more often than recovered participants. At follow-up, one-third of the participants were not recovered. This emphasizes the need for injury prevention programs for runners. More knowledge on the role of running in knee OA seems important, given the high number of participants with knee OA symptoms.